Presentation with perforation of the terminal ileum and acute limb ischemia in Crohn's disease: A case report. (March 2021) - Haddad, Anis; Ben Mahmoud, Ahmed; Chaker, Youssef; Zehani, Alia; Ksantini, Rachid; Kacem, Montasser Jameleddine
Highlights: Crohn's disease may be revealed by serious complications. Initial free peritoneum perforation in Crohn's disease is uncommon and remains life threatening. Thromboembolic events revealing Crohn's disease is exceptional. Our case is unique because of the association of two initial rare conditions revealing Crohn's disease. Abstract: Introduction and importance: Crohn's disease is a chronic inflammatory bowel disease with complex pathophysiology and multiple complications, some of which can be fatal. We report herein the management of an unusual case of Crohn's disease revealed by two life-threatening complications. Case presentation: A 59-year-old patient presented with an acute abdominal pain evolving for one day with a clinical presentation in favor of peritonitis by perforation of the last ileal loop and acute limb ischemia. At emergency laparotomy, we found a fecal peritonitis by perforation of the last ileal loop. The patient underwent an ileo-caecal resection with rifle barrel ileo-colostomy associated with embolectomy using a Fogarty catheter of the femoral artery. Pathological examination of the specimen showed an aspect consistent with an ileo-caecal Crohn's disease and blood clot embolus of the femoral artery. Postoperative course was uneventful and the patient was kept in remission with immunosuppressants. Discussion: Several complications may arise during the evolution of the disease. However, Life-threatening complication scarcely inaugurate crohn's disease like in our patient. Free perforation of the small intestine in crohn's disease occurs rarely, which makes its statistical study difficult. Risk factors for perforation are still poorly identified. Patients diagnosed with crohn's disease have a higher risk of thromboembolic complications. Indeed, there is an association between the activity of the disease and thromboembolic events. In our case, the severity of the clinical presentation as well as its inaugural character are unique. Conclusion: The management of inaugural two uncommon acute conditions in Crohn's disease is challenging.